2015
DOI: 10.1155/2015/526969
|View full text |Cite
|
Sign up to set email alerts
|

Wing Morphometry and Acoustic Signals in Sterile and Wild Males: Implications for Mating Success in Ceratitis capitata

Abstract: The sterile insect technique (SIT) is widely utilized in the biological control of fruit flies of the family Tephritidae, particularly against the Mediterranean fruit fly. This study investigated the interaction between mating success and morphometric variation in the wings and the production of acoustic signals among three male groups of Ceratitis capitata (Wiedemann): (1) wild males, (2) irradiated with Co-60 (steriles), and (3) irradiated (steriles) and treated with ginger oil. The canonical variate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…In line with these different behaviors, our interspecific PCA separated C. capitata and D. melanogaster (courtship songs) from M. domestica (mating strike) along PC2 that explained about 20% of the shape variation and captured differences in the ratio of wing width and wing length. Hence, the longer and narrower wings of M. domestica might be under selection for better flight performance (Alves and Bélo, 2002;Shyy et al, 2013), while the shorter and rounder wings of D. melanogaster and C. capitata seem to be better suited to displace more air for repeated buzzing (Burk and Webb, 1983;Webb et al, 1983;Wheeler et al, 1988;Talyn and Dowse, 2004;de Souza et al, 2015). Despite this potential link between interspecific wing shape differences and mating behavior, our data revealed that all three species were equally separated along PC1 that captured wing width along the proximal-distal axis and explained about 77% of the variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with these different behaviors, our interspecific PCA separated C. capitata and D. melanogaster (courtship songs) from M. domestica (mating strike) along PC2 that explained about 20% of the shape variation and captured differences in the ratio of wing width and wing length. Hence, the longer and narrower wings of M. domestica might be under selection for better flight performance (Alves and Bélo, 2002;Shyy et al, 2013), while the shorter and rounder wings of D. melanogaster and C. capitata seem to be better suited to displace more air for repeated buzzing (Burk and Webb, 1983;Webb et al, 1983;Wheeler et al, 1988;Talyn and Dowse, 2004;de Souza et al, 2015). Despite this potential link between interspecific wing shape differences and mating behavior, our data revealed that all three species were equally separated along PC1 that captured wing width along the proximal-distal axis and explained about 77% of the variation.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between male wing shape and mating success has been established in C. capitata because males with wider wings copulated more often successfully (de Souza et al, 2015). Interestingly, males with elongated wings have a higher mating success in D. melanogaster (Menezes et al, 2013), showing that intra-sex variation in wing shape are caused by species-specific processes.…”
Section: Sexual Dimorphism In Wing Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic abnormalities can be seen from damage to the wing which results in the reduced ability of radiated male to fly, so that the fly does not have the ability to attract attention. This statement was reinforced by de Souza et al (2015), when approaching male insects of the Tephritidae family involving multimodal signals consisting of movement with the head (visual signal), wing vibrations (sound signals), and release of pheromones (chemical signals). Based on the research of Benelli et al (2013), about the effect of wing vibrations on mating behavior of fruit flies B. oleae, the vibrations of male fruit fly wings play an important role when approaching female fruit flies.…”
Section: The Effect Of Irradiation On Total Of Matingmentioning
confidence: 99%
“…Certain points are placed in a specific order at the intersections of the wings and form two-dimensional shapes in the coordinate system, which are then evaluated using various statistical methods [44]. In the last two decades, GM has been used very successfully in the study of the genetic variability of various organisms, especially in insects of the order Diptera [45][46][47][48][49][50][51]. Lemic et al [52] studied the influence of the various agroecological conditions of mandarin cultivation on the wing shape of the medfly and demonstrated that similar environmental conditions favor wing shape similarity, which reinforced the panmictic population in a specific geographic area.…”
Section: Introductionmentioning
confidence: 99%